A new blind ECDSA scheme for bitcoin transaction anonymity - Yi, Xun (2020)
In this paper, we consider a scenario where a bitcoin liquidity provider sells bitcoins to clients. When a client pays for a bitcoin online, the provider is able to link the client's payment information to the bitcoin sold to that client. To address the privacy concerns of clients, we require that the bitcoin provider cannot tell the relationship between the real identities of clients and the sold bitcoins in the blockchain. This requirement can be effectively achieved by using blind signatures. However, existing blind signature schemes are incompatible with the Elliptic Curve Digital Signature Algorithm (ECDSA) which is used by most of the existing bitcoin protocol, thus cannot be applied directly in Bitcoin. In this paper, we propose a new blind signature scheme that allows generating a blind signature compatible with the standard ECDSA. Afterwards, we make use of the new scheme to achieve bitcoin transaction anonymity. The new scheme is built on a variant of the Paillier cryptosystem and its homomorphic properties. As long as the modified Paillier cryptosystem is semantically secure, the new blind signature scheme has blindness and unforgeability.